Creating APIs with Python - Django REST Framework - Walter, Nick (Packt Publishing, 2021)
Make RESTful web APIs for mobile applications and front-end JavaScript frameworks with JSON, XML, CSV, and authentication tokens About This Video Learn what REST APIs are and how to use them Create a Reddit clone with API calls to make and delete posts, vote on posts, and more Add API functionality to an existing Django project In Detail Django REST framework is a powerful and flexible toolkit for building web APIs. In this course, we'll be using the Django REST framework to create Python APIs. We'll first learn what REST APIs are and how to use them. Then we'll move on to creating a Reddit clone with API calls to make and delete posts, vote on posts, and more. Then, in section 3, we'll add API functionality to an existing Django project. In this case, we will use a Todo Woo project; you can practice with any of your existing Django projects. By the end of the course, you will be able to create APIs with Python using Django REST Framework.